Assess the nutritional value of faba bean (Vicia faba) and peas (Pisum sativum) residue in nylon bags (In Sacco) - Dala, Tawfic; Alrahmoun, Walid; Ali, Ammar (Latakia University Journal -Biological Sciences Series, 2019)
This study was conducted to determine the chemical composition of the residues resulting from faba bean and peas (Larache - pods peel) as well as the digestion of dry matter, crude protein, and crude fiber for these wastes in nylon bags (IN SACCO) and to demonstrate the possibility of using these residues in ruminants feeding. The results showed that the chemical composition of these residues is almost identical in terms of the proportion of each of the dry matter, organic matter and ash. In terms of crude protein, faba bean residue (Larache - pods peel) has surpassed 8.69%, 7.33% respectively on the remnants of peas 6.25%, 6.06%, respectively, and significant differences at (P <0.05). On the other hand, pea residues have outperformed by crude fiber 35.8%, 28.99% respectively on faba bean residue 25.68%, 11.02% respectively. Dry matter digestion of beans and peas larvae was 49.24%, 45.57%, respectively, and significant differences. The digestibility of dry matter in bean husks was 64.75% higher than that of peas 53.37% and significantly higher. Organic matter digestibility of faba bean residues was 69.89%, 86.61% respectively, while the residue of peas has been 58.36%, 66.12% respectively. The study concluded that the residues of both crops have a good nutritional value and can be used to feed ruminants, noting that the nutritional value of faba bean residues exceeds the nutritional value of peas. أجريت هذه الدراسة لتحديد التركيب الكيميائي للمخلفات الناتجة عن محصولي الفول والبازلاء (العرائش – قشور القرون) وكذلك معاملات هضم المادة الجافة، البروتين الخام والألياف الخام لهذه المخلفات بطريقة أكياس النايلون (IN SACCO) ولبيان إمكانية استخدام هذه المخلفات في تغذية المجترات. وقد بينت النتائج أن التركيب الكيميائي لتلك المخلفات متماثل تقريباً من حيث نسبة كل من المادة الجافة، المادة العضوية والرماد. أما من ناحية البروتين الخام فقد تفوقت مخلفات الفول (العرائش – قشور القرون) بنسبة البروتين الخام 8.69%، 7.33% على التوالي على مخلفات البازلاء 6.25%، 6.06% على التوالي وبفروق معنوية عند (P<0.05). بالمقابل فقد تفوقت مخلفات البازلاء بنسبة الألياف الخام 35.8%، 28.99% على التوالي على مخلفات الفول 25.68%، 11.02% على التوالي. أما معامل هضم المادة الجافة لعرائش الفول والبازلاء فقد بلغ 49.24%، 45.57% على التوالي وبفروق معنوية. كذلك تفوق معامل هضم المادة الجافة في قشور الفول 64.75% على قشور البازلاء 53.37% وبفروق معنوية. معامل هضم المادة العضوية لمخلفات الفول بلغ 69.89%، 86.61% على التوالي، أما في مخلفات البازلاء فقد كان 58.36%، 66.12% على التوالي. وخلصت الدراسة إلى أن مخلفات كلا المحصولين تتميز بقيمة غذائية جيدة نوعاً ما، وأنه يمكن استخدامها في تغذية المجترات مع ملاحظة تفوق القيمة الغذائية لمخلفات الفول على القيمة الغذائية لمخلفات البازلاء.